The abolition of the wheat flour ration shops in Pakistan - Garrett, James L.; Islam, Yassir (World Bank, 2005)
Since before Independence, the Government of Pakistan had been operating wheat-flour ration shops intended to provide subsidized wheat-flour to low income groups. By the mid 1980s, the system had come under increasing attack because it was inefficient and because most of the cheap flour was not in fact reaching the intended target groups. However, fears of the political backlash from affected groups made policy makers reluctant to eliminate the program. The International Food Policy Research Institute (IFPRI) was contracted to conduct an independent evaluation of the wheat-flour ration shops. The evaluation found that more than 70 per cent of the subsidized wheat never found its way to the ration-shop consumers or subsidized bakeries. The study also found that very few poor consumers benefited from the subsidies, and that alternative measures could be taken to reduce the negative impacts of eliminating the program on the wheatflour shops and distributors. The rapid, informal communication of the findings before the formal reports were published, and at a time when the issue was being debated at the highest policy levels, provided the political cover required to eliminate the program. While not the only reason for the elimination of the ration shops, the IFPRI study, which cost around $500,000, made a significant contribution to the implementation of policies, producing net annual savings to the Government of at least $40 million.